Functional rotation and its impact on tax performance: Applied research in the General Authority for Taxation (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research aimed at finding out the effect of functional rotation on the tax performance of the employees of the General Authority for Taxes through the five-meter questionnaire prepared according to the required data. The data obtained from the research sample were analyzed. The results showed a significant effect of recycling In the tax performance, and this is evident from the proportion of his contribution to the interpretation of the total variation, which is a good indicator of the impact of functional rotation in the performance of the body sample research.